Triglyceride-glucose index: a surrogate marker of homeostasis model assessment of insulin resistance to predict diabetic nephropathy - Sania Khan; Shazia Qayyum; Muhammad Nadim Akbar Khan (Journal of the Pakistan Medical Association)
Objectives: To determine the association of triglyceride-glucose index with homeostasis model assessment of insulin resistance in type 2 diabetes mellitus patients, and to determine the association of triglyceride-glucose index with urinary albumin-to-creatinine ratio for predicting diabetic nephropathy.